SOSIALISASI MITIGASI BENCANA TANAH LONGSOR PADA SDN KEMIRI 2 DESA KEMIRI, KECAMATAN PACET KABUPATEN MOJOKERTO - Ashshiddiqi, Muhammad ilmi; Friska Ayu, Friska Ayu; Moch Sahri, Moch Sahri; Octavianus Hutapea, Octavianus Hutapea; Andhaning Pawestri, Lintang (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Indonesia is a country with a high level of vulnerability to landslide disasters due to its geographical location and complex topography. Kemiri Village, located in Pacet Subdistrict, Mojokerto Regency, is one of the landslide-prone areas that threatens the safety of the community, including elementary school students. The lack of students' understanding regarding early warning signs and evacuation procedures highlights the need for disaster mitigation education from an early age. This study aims to evaluate the effectiveness of a landslide disaster mitigation socialization activity in improving the knowledge of students at SDN Kemiri 2. The research employed a descriptive quantitative method using a pre-test and post-test design. The subjects were 11 fifth-grade students who participated in the socialization activity on June 19, 2025. Data were collected through closed-ended questionnaires and analyzed descriptively and statistically using a paired sample t-test. The results showed a significant increase in students’ knowledge after the socialization. Prior to the activity, 63.6% of students were in the "poor" category, and only 9.1% were in the "good" category. After the activity, 54.5% were in the "good" category and 36.4% reached the "excellent" category. Statistical analysis indicated a significance value of p < 0.005, confirming the improvement was significant. It can be concluded that the socialization activity effectively improved students’ preparedness for landslide disasters. This program is recommended for continuous implementation, especially in schools located in disaster-prone areas.